SGLT2i alleviates epicardial adipose tissue inflammation by modulating ketone body–glyceraldehyde-3-phosphate dehydrogenase malonylation pathway. Issue 4 (2nd April 2023) - Li, Lina; Hua, Cuncun; Liu, Xiaoyan; Wang, Yidan; Zhao, Lei; Zhang, Yeping; Wang, Li; Su, Pixiong; Yang, Min-Fu; Xie, Boqia
Abstract : Aims: Inflammation in the epicardial adipose tissue (EAT) is a contributor to atrial fibrillation. Studies have reported that sodium glucose co-transporter 2 inhibitor (SGLT2i) can alleviate EAT inflammation. However, the mechanism remains elusive. This study aims to investigate the molecular mechanism of SGLT2i in reducing EAT inflammation and to explore the effects of SGLT2i on atrial fibrosis in atrial fibrillation. Methods: Sprague–Dawley rats were injected with angiotensin II to induce atrial fibrillation and randomly assigned to receive SGLT2i ( n  = 6) or vehicle ( n  = 6). Macrophages (RAW264.7) were treated with ketone bodies; ACC1 knockdown/overexpression and malonyl-CoA overexpression were performed in vitro . The levels of inflammatory cytokines, ACC1, and malonyl-CoA were examined by ELISA. GAPDH malonylation was measured by co-immunoprecipitation. Results: In atrial fibrillation rats, SGLT2i increased the ketone body levels and decreased the expression of ACC1 and alleviated EAT inflammation and atrial fibrosis. In RAW264.7 cells, ketone bodies decreased the levels of ACC1, malonyl-CoA, and GAPDH malonylation, accompanied by reduced inflammatory cytokines. ACC1 knockdown decreased the expression of malonyl-CoA and GAPDH malonylation and alleviated lipopolysaccharide (LPS)-induced macrophage inflammation; these effects were inhibited by malonyl-CoA overexpression. Furthermore, the protective effects of ketone bodies on macrophage inflammation were abrogated by ACC1 overexpression. Conclusion: SGLT2i alleviates EAT inflammation by reducing GAPDH malonylation via downregulating the expression of ACC1 through increasing ketone bodies, thus attenuating atrial fibrosis.